Innovation in Public Services Through the Kawi Smara Program at Klungkung Regency - Ida Ayu Putu Sri Widnyani; I Made Siswa (Indonesian Association for Public Administration (IAPA), 2019)
This study aims to determine (1) the effectiveness of the Kawi Smara Innovation Program in improving the quality of public services at Klungkung Regency (2) factors are the inhibitors of the effectiveness of the Kawi Smara Innovation Program in improving the quality of public at Klungkung Regency. This study employed the qualitative descriptive methodology. The results of this study indicate that (1) the implementation of Kawi Smara's innovation program has been effective in terms of service quality, this innovation program has proven to greatly facilitate the public to obtain a marriage certificate, this innovation program has advantages in terms of the speed of the marriage certificate. the solution for the people who want to do their marriage ceremony right away is to get their marriage certificate. The Kawi Smara program is not maximally in quantity, the target of Kawi Smara's innovation program has not been maximally achieved, this is evidenced by the still low percentage of people who follow Kawi Smara's innovative program services. (2) Factors that hinder the effectiveness of the Kawi Smara innovation program at Klungkung Regency based on the results of the study are Lack of socialization, low public awareness and budget constraints.